Question
upstudy study bank question image url

Qiven the fellowing functions: \[ g(x)=x+2 \quad f(x)=x^{2}-5 \] Find the fellewing 1. \( g(-2)=0 \) 2. \( g(0)= \) 3. \( f(-2)=1 \) 4. \( f(0)=-5 \) 5. The range of \( g \) when the domain is -1 , 6. The range of i when the domain is 1 .

Ask by Schwartz Carlson. in the United States
Mar 11,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

1. \( g(-2) = 0 \) 2. \( g(0) = 2 \) 3. \( f(-2) = -1 \) 4. \( f(0) = -5 \) 5. The range of \( g \) when the domain is \(-1\) is \(\{1\}\). 6. The range of \( f \) when the domain is \(1\) is \(\{-4\}\).

Solution

Let's solve the problem step by step for each of the given functions \( g(x) \) and \( f(x) \). ### Given Functions: 1. \( g(x) = x + 2 \) 2. \( f(x) = x^2 - 5 \) ### 1. Find \( g(-2) \) To find \( g(-2) \), we substitute \(-2\) into the function \( g(x) \): \[ g(-2) = -2 + 2 \] Calculating this gives: \[ g(-2) = 0 \] ### 2. Find \( g(0) \) Next, we find \( g(0) \): \[ g(0) = 0 + 2 \] Calculating this gives: \[ g(0) = 2 \] ### 3. Find \( f(-2) \) Now, we substitute \(-2\) into the function \( f(x) \): \[ f(-2) = (-2)^2 - 5 \] Calculating this gives: \[ f(-2) = 4 - 5 = -1 \] ### 4. Find \( f(0) \) Next, we find \( f(0) \): \[ f(0) = 0^2 - 5 \] Calculating this gives: \[ f(0) = 0 - 5 = -5 \] ### 5. Find the range of \( g \) when the domain is \(-1\) Since the domain is a single value \(-1\), we find: \[ g(-1) = -1 + 2 \] Calculating this gives: \[ g(-1) = 1 \] Thus, the range of \( g \) when the domain is \(-1\) is \(\{1\}\). ### 6. Find the range of \( f \) when the domain is \(1\) Since the domain is a single value \(1\), we find: \[ f(1) = 1^2 - 5 \] Calculating this gives: \[ f(1) = 1 - 5 = -4 \] Thus, the range of \( f \) when the domain is \(1\) is \(\{-4\}\). ### Summary of Results: 1. \( g(-2) = 0 \) 2. \( g(0) = 2 \) 3. \( f(-2) = -1 \) 4. \( f(0) = -5 \) 5. The range of \( g \) when the domain is \(-1\) is \(\{1\}\). 6. The range of \( f \) when the domain is \(1\) is \(\{-4\}\).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

Let’s break it down! To find \( g(0) \), substitute \( x = 0 \) into \( g(x) = x + 2 \). So, \( g(0) = 0 + 2 = 2 \). Now for \( f(-2) \), substitute \( x = -2 \) into \( f(x) = x^{2} - 5 \). Thus, \( f(-2) = (-2)^{2} - 5 = 4 - 5 = -1 \). Moving on to \( f(0) \), substituting \( x = 0 \) gives us \( f(0) = 0^{2} - 5 = -5 \), which we've already noted! When determining the range of \( g(x) \) with the domain as \(-1\), simply plug in \(-1\). So, \( g(-1) = -1 + 2 = 1 \). The output is one value, thus, the range here is just \( \{1\} \). For \( f(x) \) with a domain of \( 1 \), calculate \( f(1) = 1^{2} - 5 = 1 - 5 = -4 \). The output again is singular, leading to a range of \( \{-4\} \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy